Performance of Some Stochastic Restricted Ridge Estimator in Linear Regression Model - Jibo Wu; Chaolin Liu (Journal of Applied Mathematics)
This paper considers several estimators for estimating the stochastic restricted ridge regression estimators. A simulation study has been conducted to compare the performance of the estimators. The result from the simulation study shows that stochastic restricted ridge regression estimators outperform mixed estimator. A numerical example has been also given to illustrate the performance of the estimators.